2024
DOI: 10.18063/ijb.v6i3.275
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Gene-activated Octacalcium Phosphate Implants for Large Bone Defects Engineering

Abstract: The aim of the study was the development of three-dimensional (3D) printed gene-activated implants based on octacalcium phosphate (OCP) and plasmid DNA encoding VEGFA. The first objective of the present work involved design and fabrication of gene-activated bone substitutes based on the OCP and plasmid DNA with VEGFА gene using 3D printing approach of ceramic constructs, providing the control of its architectonics compliance to the initial digital models. X-ray diffraction, scanning electron microscopy (SEM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, the above‐mentioned bioactive substances are not suitable for high‐temperature printing (SLS and FDM) or stents requiring high‐temperature post‐treatment. Fortunately, loading bioactive substances in the 3D printed scaffolds after AM is considered as a solution to the above limitations, for example, the good developments of loading genes, [ 274,275 ] drugs [ 276 ] and proteins [ 277 ] have been made in bone regeneration.…”
Section: Future Prospectsmentioning
confidence: 99%
“…In addition, the above‐mentioned bioactive substances are not suitable for high‐temperature printing (SLS and FDM) or stents requiring high‐temperature post‐treatment. Fortunately, loading bioactive substances in the 3D printed scaffolds after AM is considered as a solution to the above limitations, for example, the good developments of loading genes, [ 274,275 ] drugs [ 276 ] and proteins [ 277 ] have been made in bone regeneration.…”
Section: Future Prospectsmentioning
confidence: 99%
“…We have previously demonstrated that an OCP-based bone substitute could improve reparative osteogenesis in vivo (Komlev et al, 2014 ; Bozo et al, 2020 ). However, a lack of osteoinductive capacities has been observed in experimental studies, which could explain why a significant part of the newly formed tissues in the biopsy samples was presented by fibrous tissue in the clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, an nHA-collagen scaffold has been reported to accelerate bone regeneration with sustained localized delivery of angiogenic (pVEGF) and osteogenic (pBMP2) genes [42]. Moreover, the potential clinical usefulness of 3D printed GAM based on octacalcium phosphate (OCP) and pVEGF has been shown in the regeneration of large bone defects [43]. Therefore, many challenges in establishing GAM-based bone engineering need to be overcome by further investigating both the target genes in a nanoball and the biodegradable matrices.…”
Section: Discussionmentioning
confidence: 99%